Effects of radiofrequency on muscle tissue regeneration - da Silva, Rodrigo Marcel Valentim; Cavalcanti, Rafael Limeira; Félix, Bruno Felipe Soares; Coutinho Santos, Rodney Wordnei; da Cunha, Tamara Martins; Ronzio, Oscar Ariel; Meyer, Patrícia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Radiofrequency (RF) is recommended to treat pathologies with the presence of inflammation, as it induces diathermy and, consequently, promotes better oxygenation, nutrition and local vasodilation. Objective: Evaluate the effect of RF on muscle regeneration in Wistar rats. Methods: It is a controlled and randomized experiment, with a sample composed of 40 Wistar rats, divided equally into four groups: G1 (control group), G2 (lesion, without RF), G3 (RF after 72 hours of lesion) and G4 (RF after 7 days of lesion), all sacrificed 21 days after the injury. The RF parameters used were: Sine wave; frequency of 0.5MHz; 5 cm² treatment area on the region around the lesion; power of 45%; two-minute application; intensity of 15 seconds to heat the head, 1 minute at 20% and another minute at 10%. An optical microscope was used for histological analysis and, for the biomechanical properties (maximum elongation and maximum load), the mechanical traction test of the gastrocnemius muscles. For statistical analysis, the two-way ANOVA test and the Benferroni test were used, considering 5% of significance. Results: It was observed in G3 that the inflammatory process was optimized by the RF when compared to the other groups, presenting intact muscle fibers with a discreet regeneration process. G4, on the other hand, revealed intense inflammation with significant granulation tissue, as well as fibrosis and healing. As for the biomechanical characteristics, there were no statistically significant differences in the intergroup comparison. Conclusion: RF was more effective when applied after 72 hours after the injury, in addition to not interfering with muscle biomechanical characteristics.